Changes in Ovarian Tissue Structure Following Saturation with 1,2-Propanediol in Media of Various Compositions - Trutayeva, Irina A.; Kiroshka, Viktoriya V.; Bozhkova, Yuliya O.; Bondarenko, Tatyana P. (Problems of Cryobiology and Cryomedicine, 2016)
One of the most promising technologies of preserving fertility in women with ovarian pathologies of various origins is the transplantation of cryopreserved ovarian tissue. Wide introduciton of this technology into a clinical practice requires the optimizing of freeze-thawing protocols. One of the stages of improving the cryopreservation process is the enhancing of osmotic tolerance of cells in the tissue when adding the cryoprotective solutions. In this research there was comparatively analyzed the dynamics of volu-metric and morphological transformation of ovarian tissue at its gradual saturation with the 1,2-PD (1.5–3 M) in the media of different composition. The preservation of follicle structure integrity in the final concentration of 1,2-PD (3 M) was found to be dependent on quantitative ratios of electrolyte and non-electrolyte components of the initial medium. An increase in the initial medium osmolarity by introducing a non-electrolyte component (sucrose) resulted in a decrease in the volume of oocytes and maintaining of cell-to-cell contacts of the follicle structural components. Probl Cryobiol Cryomed 2016; 26(1):53-62.